2015
DOI: 10.1371/journal.pone.0140015
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Oomycide Oxathiapiprolin Inhibits All Stages in the Asexual Life Cycle of Pseudoperonospora cubensis - Causal Agent of Cucurbit Downy Mildew

Abstract: Oxathiapiprolin is a new oomycide (piperidinyl thiazole isoxazoline class) discovered by DuPont which controls diseases caused by oomycete plant pathogens. It binds in the oxysterol-binding protein domain of Oomycetes. Growth chambers studies with detached leaves and potted plants showed remarkable activity of oxathiapiprolin against Pseudoperonospora cubensis in cucurbits. The compound affected all stages in the asexual life cycle of the pathogen. It inhibited zoospore release, cystospore germination, lesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 33 publications
2
66
0
Order By: Relevance
“…Previous research indicated that OX exhibited direct and high inhibition activity against the growth of many oomycete pathogens with a low dose. The target protein of OX was the oxysterol binding protein (OSBP) in oomycetes [33][34][35][36][37]. Besides, OX exhibited both curative and protective activity against pepper Phytophthora blight, and the protective activity was better [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research indicated that OX exhibited direct and high inhibition activity against the growth of many oomycete pathogens with a low dose. The target protein of OX was the oxysterol binding protein (OSBP) in oomycetes [33][34][35][36][37]. Besides, OX exhibited both curative and protective activity against pepper Phytophthora blight, and the protective activity was better [37].…”
Section: Discussionmentioning
confidence: 99%
“…Oxathiapiprolin (OX), a piperidinyl thiazole isoxazoline fungicide, was synthesized by DuPont Company in 2007 [32,33]. OX was developed as an oomycete inhibitor with a high inhibition activity against many oomycetes, including Phytophthora capsici, Phytophthora infestans, Phytophthora sojae, Phytophthora parasitica, Phytophthora nicotianae, Pseudoperonospora cubensis, and Pythium ultimum [34][35][36][37]. Previous study showed that OX could interact with the oxysterol binding protein (OSBP) in oomycetes, which indicated that OSBP might be the target protein of OX [33].…”
Section: Introductionmentioning
confidence: 99%
“…Oxathiapiprolin (Fig. ), is the first member of a novel class of piperidinyl thiazole isoxazoline fungicides with exceptionally high activity against diseases caused by Oomycete pathogens. Via a novel target for fungicides, it inhibits an oxysterol‐binding protein resulting in excellent preventive, curative and residual efficacy against diseases in grapes, potatoes and vegetables at low use rates …”
Section: Fungicidesmentioning
confidence: 99%
“…Isoxazole is one of the top 10 % heterocycles frequently used in drug discovery , . Derivatives of this heterocycle are widespread among natural products; they are represented by antirheumatic and antiviral drugs, fungicides, and hypoglycemic agents . Isoxazole‐based sulfonamide antibiotics can be found in the World Health Organization model list of essential medicines…”
Section: Introductionmentioning
confidence: 99%